FAKTOR-FAKTOR YANG MEMENGARUHI KEJADIAN STUNTING DI DESA TEMUROSO KECAMATAN GUNTUR KABUPATEN DEMAK - Yuli Astuti; Isna Hudaya; Ratih Dwi Handayani (LPPM STIKES BINA GENERASI POLEWALI MANDAR, 2023)
Stunting is a condition of failure to thrive in toddlers or children as a result of long-term malnutrition where having a height of less than -2SD for children of their age is also said to be abnormal in the growth process. The stunting incident in Temuroso Village, Kec. Guntur Kab. Demak has experienced an increase from 137 cases in 2020 to 156 cases in 2022. The purpose of this study was to determine the factors that influence the incidence of stunting in Temuroso Village, Kec. Guntur Kab. Demak. This type of research is analytic observational using a case-control design with a total sample of 46 in the case group and 46 in the control group selected by purposive sampling technique. The data analysis used was univariate and bivariate analysis using the chi-square test. The results showed that there was a relationship between the accuracy of giving complementary foods to the incidence of stunting with a significance value of p=0.018, not related to the incidence of stunting, namely a history of exclusive breastfeeding (p=0.692) and economic status (p=0.195). The conclusion of this study is that toddlers in Temuroso Village, Guntur District, Demak Regency tend to be given complementary foods in an inappropriate way. It is hoped that health workers will pay more attention to the method and accuracy in giving complementary foods through counseling and education from an early age to mothers so that they can reduce the risk of stunting in Temuroso Village, Kec. Guntur Kab. Demak.